Anatomically based 3D geometric modeling of specific biological structures - Tihacek-Sojic, Lj., University of Belgrade, Belgrade (Serbia). School of Dentistry; Milic, A., University of Belgrade, Belgrade (Serbia). School of Dentistry; Zivkovic, R., University of Belgrade, Belgrade (Serbia). School of Dentistry; Ilic, J., University of Belgrade, Belgrade (Serbia). School of Dentistry (Acta veterinaria (Beograd), 2007)
The aim of this paper was to to present the development of our own three-dimensional tooth model created for finite element analyses of intact tooth behaviour under functional loading. Also, the idea was to evaluate the possibility for using finite element analysis in veterinary biomechanical research. Our own 3D model was created using computer software according to available literature data, and facts gained from freshly extracted intact teeth and plaster models. It is necessary to emphasize that FEM is an effective tool that has been adapted from the engineering arena to biomechanic research and has the potential to contribute to the growing scientific basis of knowledge in veterinary dentistry.